A meta-analysis of video-assisted thoracoscopic decortication versus open thoracotomy decortication for patients with empyema - Pan, Hui; He, Jiaxi; Shen, Jianfei; Jiang, Long; Liang, Wenhua; He, Jianxing (Journal of thoracic disease, 2017)
Thoracic pleural empyema is a collection of pus within a thoracic cavity. In stage 2 (fibrinopurulent) and stage 3 (organizational), decortication is the only choice. But there is no consensus on whether to choose video-assisted thoracoscopic decortication (VATD) or open thoracotomy decortication (OTD). We sought to answer this question by performing a meta-analysis. Six electronic databases were searched. Primary outcomes were operative time, postoperative hospital stay, prolonged air leak, chest tube duration, relapse rate, morbidity and mortality. Review Manager (RevMan) [Computer program]. Version 5.2, 2014 was used to pool the data. Subgroup analysis and publication bias analysis were also conducted. The operative time [mean difference -36.89; 95% confidence interval (CI), -60.96 to -12.82; P=0.003], postoperative hospital stay (mean difference -2.41; 95% CI, -3.74 to -1.09; P=0.0004), prolonged air leak (9.7% 17.1%; RR 0.56; 95% CI, 0.33 to 0.94; P=0.03), chest tube duration (mean difference -1.52; 95% CI, -2.55 to -0.48; P=0.004), morbidity (16.4% 24.5%; RR 0.62; 95% CI, 0.44 to 0.88; P=0.007) and mortality (4.1% 6.2%; RR 0.47; 95% CI, 0.26 to 0.86; P=0.01) of VATD were statistically less than the OTD. In terms of relapse rate, there was no statistical significance between two surgical approaches (7.2% 4.2%; RRN1.28; 95% CI, 0.39 to 4.15; P=0.68). The present study summarized and compared the clinical outcomes of VATD versus OTD for the empyema patients. The current data showed that VATD might be comparable or even better than OTD in terms of operative time, postoperative hospital stay, chest tube duration, prolonged air leak rate, morbidity and mortality. But referring to the relapse rate, there was no statistical significance. The results from analysis was subject bias because of prospective randomized studies were not selected. However, VATD could be implemented safely as first-line management for most of empyema.